Delivering Infrastructure Projects: What Makes Ppp The Preferred Method? - Dr. Mohit Kumar Ojha; CA Priti Sharma; Aanchal Sharma Lamba (Elementary Education Online, 2023)
In the developing world, India is the largest market for private infrastructure investment as a result of policies and programs implemented by the Central and State governments. According to the World Bank's report on private infrastructure investment, India has been the top receiver of PPI (private sector participation in infrastructure) since 2006. There were 1,065 public-private partnership (PPP) projects funded by the central government in February 2018, worth INR 2,55,116 crore. Given that public-private partnerships (PPPs) are now the most popular way to build infrastructure, it's vital to investigate what makes PPPs superior to other approaches and what the most notable advantages of PPPs are. Research is now being done to assess the advantages and disadvantages of participating in a public-private partnership (PPP).